FDI inflows, price and exchange rate volatility: New empirical evidence from Latin America - Silvia Dal Bianco; Cong To Loan Nguyen (International Journal of Financial Studies, 2017)
This paper investigates the impact of price and real exchange rate volatility on Foreign Direct Investment (FDI) inflows in a panel of 10 Latin American and Caribbean countries, observed between 1990 and 2012. Both price and exchange rate volatility series are estimated through the Generalized Autoregressive Conditional Heteroscedasticity model (GARCH). Our results obtained, employing the Fixed Effects estimator, confirm the theory of hysteresis and option value, in so far as a statistically significant negative effect of exchange rate volatility on FDI is found. Price volatility, instead, turns out to be positive but insignificant. Moreover, we show that human capital and trade openness are key for attracting foreign capital. From the policy perspective, our analysis suggests the importance of stabilization policies as well as the policy of government credibility in promoting trade openness and human capital formation.
Keywords: C33; F21; F23; 330; FDI; GARCH; real exchange rate and price volatility; Latin America and the Caribbean